Corrosion of coupled steels with different microstructures in concrete environment. (10th April 2018) - Torbati-Sarraf, H.; Poursaee, A.
Highlights: The galvanic connection between TMT and conventional reinforcement steel in chloride-contaminated concrete pore solution led to significant increase in the corrosion of steel reinforcement. Individual TMT steel specimens showed superior corrosion resistance compared to the conventional steel specimens. When coupled, the conventional steel showed better passivation compared to the TMT steel in chloride-free pore solution. When chloride added, the TMT steel became the anode and their corrosion activity increased compared to the conventional steel. Abstract: This study investigated the electrochemical behavior of two carbon steels with different microstructures, i.e. thermomechanical treated (TMT) steel and conventional steel, and the influence of galvanic coupling between them on their corrosion performance in simulated concrete pore solution. The specimens were immersed in the chloride-free pore solution for 30 days and then 3% by weight of NaCl was added to the solution. The specimens were then kept in the chloride-contaminated solution for 50 days. The corrosion resistance of the specimens were assessed by different electrochemical measurement techniques. An increase in the overall corrosion was observed in the coupled specimens compared to the individual specimens. The results of the electrochemical experiments showed that while the individual thermomechanical treated steel specimens showed superior corrosion resistance compared to the conventional steel specimens when coupled, they became the anode and their corrosion activity increased compared to the conventional steel.